PREPARASI MANGAN OKSIDA HASIL PERTUKARAN KATION Mg 2+ DENGAN K-BIRNESSITE YANG DISINTESIS MENGGUNAKAN REDUKTOR GLUKOSA - Afra Juwita; Amir Awaluddin; Akmal Muchtar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Todorokite is a family of tunneled manganese oxide with 3x3 tunnel framework. It could beprepared through a precursor Mg-birnessite by reflux method. In this study, K-birnessite was prepared by ceramic routes using glucose as reducing agent. K-birnessite was then ion-exchanged with Mg 2+ to form Mg-birnessite. The typical reaction conditions for ion-exchanged K + with Mg 2+ were as follows: contact times of 10, 12, 14, 16 and 18 hours with 16 hours for the optimum replacement ion K + with ion Mg 2+ . The total replacement of ion K + by ion Mg 2+ was 94,32%. Data from the X-ray diffraction pattern showed the formation of todorokite at 2Ө = 9,02o with d-spacing 9,79Å, but the peak for K-birnessite also appeared at an angle 2Ө = 12,57o with d-spacing 7,03Å. Thermal analysis of Mg-birnessite was observed by TG-DTA curve that showed the weight loss of Mg-birnessite about 20%. DTA curve also showed endotermic peak at 900oC, which indicated the transformation phase from layered to tunneled structure.